Times hearing effects caused by overuse of headphones (Research, Society and Development, 2021)
The habit of using headphones has been growing gradually in people's lives, especially among the young audience. In view of the lack of information about the harm caused by the incorrect use of headphones, this article aims to report on the possible consequences for hearing health that users are exposed to. This is an integrative literature review where several articles were selected using the platforms of Google Scholar, LILACS, SCIELO. An estimate by the World Health Organization shows that about 5% of hearing losses in Brazil, approximately 1.5 million people, are related to the misuse of headphones. Irregular use of headphones causes a series of risks to people´s hearing health, which can cause hearing loss and rinring in the ear.